The Influence of Using Historical Domino Card Learning Media on the Chronological Thinking Skills of Grade X Students of SMA Negeri 1 Martapura - Usnul Khotimah; Melisa Prawitasari; Sriwati Sriwati (JURNAL PENDIDIKAN IPS, 2025)
Chronological thinking is a crucial skill in history learning, as it enables students to understand the sequence of time and the logical relationship between historical events. Preliminary observations at SMA Negeri 1 Martapura revealed that many students still face difficulties in this aspect, partly due to the limited use of interactive learning media. This study aims to analyze the effect of using domino card media on students’ chronological thinking skills. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. The sample consisted of class X.2 as the experimental group and class X.4 as the control group. The research instrument was a set of 21 multiple-choice questions that had been tested for validity and reliability. Data analysis was conducted using normality, homogeneity, and t-tests with the assistance of IBM SPSS 25. The results showed that the average pretest score of the experimental class was 65.25, which increased to 84.57 in the posttest, while the control class only increased slightly from 66.89 to 69.18. The independent sample t-test revealed a significance value of 0.000 < 0.05, indicating that the alternative hypothesis was accepted. Therefore, it can be concluded that historical domino card media has a significant effect on improving students’ chronological thinking skills in history learning.